Host RNA-binding proteins as broad-spectrum targets for antiviral therapy - Sagnik Biswas (npj Viruses, 2026)
Abstract RNA-binding proteins (RBPs) regulate key host processes and facilitate viral replication. Certain antiviral RBPs limit infection and trigger immune responses. Targeting these proteins could yield broad-spectrum antiviral activity with a lower risk of resistance. Nonetheless, translating this approach into clinical use requires balancing antiviral activity with the preservation of essential host functions. This review explores current RBP-directed antivirals and considers key challenges and future research directions.